Cost-effectiveness of empagliflozin in the UK in an EMPA-REG OUTCOME subgroup with type 2 diabetes and heart failure - Reifsnider, Odette S.; Kansal, Anuraag R.; Franke, Jennifer; Lee, Joseph; George, Jyothis T.; Brückmann, Martina; Kaspers, Stefan; Brand, Sarah B.; Ustyugova, Anastasia; Linden, Stephan; Stargardter, Matthew; Hau, Nikco (ESC heart failure, 2020)
Aims Heart failure (HF) and type 2 diabetes (T2D), common co-morbidities, translate into worse patient prognoses and higher direct costs than for either condition alone. Empagliflozin has been shown to markedly reduce cardiovascular (CV) deaths and HF hospitalizations (HHF) in HF patients with T2D. This study evaluated the lifetime cost-effectiveness of supplementing standard of care (SoC) with empagliflozin, relative to SoC alone, in HF patients with T2D from the UK payer perspective. Methods and results An existing discrete-event simulation model was adapted for the economic evaluation. Risk equations developed from time-dependent parametric survival analyses using patient-level HF subpopulation data from the EMPA-REG OUTCOME trial were employed to predict CV and renal events. Non-CV death, utility weights, and costs were drawn from UK sources. Quality-adjusted life years (QALYs) and costs were discounted at 3.5% per annum. Relative to SoC, empagliflozin with SoC yielded fewer first HHF, recurrent HHF, CV death, and non-fatal myocardial infarction but more non-fatal stroke events. Empagliflozin with SoC vs. SoC alone was associated with increased average life expectancy (10.80 vs. 9.59 LYs) and quality of life (6.27 vs. 5.62 QALYs), though at higher lifetime cost (£18 197 vs. £16 829) per person, resulting in an incremental cost-effectiveness ratio of £2093 per QALY. The probability of empagliflozin being cost-effective in the HF subpopulation at a £20 000 per QALY willingness-to-pay threshold was 91%. Conclusions This analysis suggests that adding empagliflozin to SoC in HF patients with T2D constitutes a cost-effective use of UK healthcare resources and may provide long-term health benefits to patients.
Gesehen am 20.10.2025